Organocatalyzed [4+2] Annulation of All‐Carbon Tetrasubstituted Alkenes with Allenoates: Synthesis of Highly Functionalized 2H‐ and 4H‐Pyran Derivatives. Issue 17 (20th October 2016) - Ngo, Thi‐Thuy‐Duong; Kishi, Kenta; Sako, Makoto; Shigenobu, Masashi; Bournaud, Chloée; Toffano, Martial; Guillot, Régis; Baltaze, Jean‐Pierre; Takizawa, Shinobu; Sasai, Hiroaki; Vo‐Thanh, Giang
Abstract: A stereoselective [4+2] annulation of acyclic all‐carbon tetrasubstituted alkenes with allenoates was described. The reaction with DABCO proceeded smoothly leading to the formation of highly functionalized 4 H ‐pyran derivatives in good yields. We have also reported first β ‐ICD‐catalyzed [4+2] annulation affording functionalized enantioenriched 2H ‐pyran derivatives bearing a chiral all‐carbon quaternary center. Abstract : First amine‐catalyzed [4+2] annulation of ethyl allenoate and all‐carbon tetrasubstituted alkenes was described. Our finding procedure afforded the highly functionalized 2H ‐ and 4H ‐pyran derivatives bearing an all‐carbon quaternary center.